Molecular and Cellular Mechanisms of Shigella flexneri Dissemination - Agaisse, Hervé (Frontiers in Cellular and Infection Microbiology, 2016)
The intracellular pathogen Shigella flexneri is the causative agent of bacillary dysentery in humans. The disease is characterized by bacterial invasion of intestinal cells, dissemination within the colonic epithelium through direct spread from cell to cell, and massive inflammation of the intestinal mucosa. Here, we review the mechanisms supporting S. flexneri dissemination. The dissemination process primarily relies on actin assembly at the bacterial pole, which propels the pathogen throughout the cytosol of primary infected cells. Polar actin assembly is supported by polar expression of the bacterial autotransporter family member IcsA, which recruits the N-WASP/ARP2/3 actin assembly machinery. As motile bacteria encounter cell-cell contacts, they form plasma membrane protrusions that project into adjacent cells. In addition to the ARP2/3-dependent actin assembly machinery, protrusion formation relies on formins and myosins. The resolution of protrusions into vacuoles occurs through the collapse of the protrusion neck, leading to the formation of an intermediate membrane-bound compartment termed vacuole-like protrusions (VLPs). VLP formation requires tyrosine kinase and phosphoinositide signaling in protrusions, which relies on the integrity of the bacterial type 3 secretion system (T3SS). The T3SS is also required for escaping double membrane vacuoles through the activity of the T3SS translocases IpaB and IpaC, and the effector proteins VirA and IcsB. Numerous factors supporting envelope biogenesis contribute to IcsA exposure and maintenance at the bacterial pole, including LPS synthesis, membrane proteases, and periplasmic chaperones. Although less characterized, the assembly and function of the T3SS in the context of bacterial dissemination also relies on factors supporting envelope biogenesis. Finally, the dissemination process requires the adaptation of the pathogen to various cellular compartments through transcriptional and post-transcriptional mechanisms.